2011
DOI: 10.1007/s10877-011-9297-x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive intracranial pressure measurement using infrasonic emissions from the tympanic membrane

Abstract: It is conceivable that the assessment of infrasonic emissions will become suitable both as a screening tool and for the continuous monitoring of ICP in an intensive care environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…[79] investigated whether measuring infrasonic emissions from the tympanic membrane could monitor ICP in 31 individuals (17 patients, 14 healthy). Invasive ICP monitoring was indicated in all patients and was done so with implanted pressure sensors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[79] investigated whether measuring infrasonic emissions from the tympanic membrane could monitor ICP in 31 individuals (17 patients, 14 healthy). Invasive ICP monitoring was indicated in all patients and was done so with implanted pressure sensors.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in ICP was stimulated by postural changes using a tilting table. [79] The infrasonic emissions were measured by recording the TMD using a probe placed in the external auditory meatus in an airtight manner. [30] It was observed that the stimulated changes in ICP were detected in waveforms both noninvasively and invasively.…”
Section: Methodsmentioning
confidence: 99%
“…Intracranial pressure measurement using tympanic membrane displacement (TMD) and infrasonic emissions: by measuring infrasonic emissions from the tympanic membrane researchers have be able to estimate in vivo and non-invasively whether the intracranial pressure is high or low. 4 Low intracranial pressure is associated with an initial high peak followed by peaks with smaller amplitudes whereas elevated intracranial pressure is associated with a significant decrease in the number of peaks and in the amplitude difference between initial and last measured peaks. This method, nevertheless, does not provide objective, numeric measurements of intracranial pressure levels, even though it could potentially be used as a screening tool and for the continuous intracranial pressure monitoring.…”
Section: How Can We Measure Intracranial Cerebrospinal Fluid (Csf) Prmentioning
confidence: 98%
“…The CAP and ECP spectra also include the interactions between the two latter components, which are located at f C À f R , f C À 2f R , f C þ f R , and so on. Figures 3(a) and 3(b) suggest that the assessment of infrasonic emissions (ECP) will someday be suitable both as a screening tool and for the continuous monitoring of ICP in an intensive care environment (Stettin et al, 2011).…”
Section: Transfer Function Between Cap and Ecpmentioning
confidence: 99%
“…Low-frequency power reflectance appears to increase systematically with increased ICP, while the corresponding transmittance decreases systematically. Paulat et al (1999) and Stettin et al (2011) investigated whether ICP can be assessed by measuring infrasonic emissions from the TM. In a total of 83 measurements, the changes in ICP that were observed in response to different types of stimulation were detected in noninvasively and invasively acquired waveforms.…”
Section: Introductionmentioning
confidence: 99%